Exploring Indonesian nurses’ perspectives on preparing parents of preterm infants for hospital discharge: A qualitative study - Hariati, Suni; Febriani, Andi Dwi Bahagia; Sutomo, Retno; Lusmilasari, Lely; McKenna, Lisa (Elsevier Ltd, 2021)
Objective: This study aimed to explore Indonesian nurses’ perspectives about their discharge preparation processes to enhance the discharge readiness of parents of preterm infants in the NICU. Methods: A descriptive qualitative study with in-depth interview was used in this study. Eight purposively sampled NICU nurses were involved; all interviews were audio-recorded, transcribed verbatim, and analysed using thematic analysis. Results: Three themes emerged that described nurses’ perceptions related to their own discharge preparation process for parents of preterm infants: (1) diversity in discharge preparation; (2) Mother-Infant interaction during daily cares; and (3) Internal and external barrier to discharge preparation. Conclusions: Nurses prepared parents of preterm infants for hospital discharge by providing health education, support systems and empowering mothers in their infant's care until they attained independence in caring for their baby prior to baby's discharge from the hospital. A multidisciplinary team with clear hospital policies and guidelines to follow along with improved nursing competence in the education and discharge process for parents of NICU babies are necessary to ensure the successful transition from the hospital NICU to home. Nurses prepared parents of preterm infants for hospital discharge by providing health education, support systems, and empowering mothers in their infant's care until they attained independence in caring for their baby prior to baby's discharge from the hospital NICU. A multidisciplinary team with clear hospital policies and guidelines to follow along with improved nursing competence are needed for successful implementation of effective discharge planning.